First Insights Into Within Host Translocation of the Bacillus cereus Toxin Cereulide Using a Porcine Model - Bauer, Tobias; Sipos, Wolfgang; Stark, Timo D.; Käser, Tobias; Knecht, Christian; Brunthaler, Rene; Saalmüller, Armin; Hofmann, Thomas; Ehling-Schulz, Monika (Frontiers in Microbiology, 2018)
Bacillus cereus is a gram-positive pathogen mainly known to evoke two types of foodborne poisonings. The diarrheal syndrome is caused by enterotoxins produced during growth in the intestine. In contrast, the emetic type is caused by the dodecadepsipeptide cereulide pre-formed in food. Usually, both diseases are self-limiting but occasionally more severe forms, including fatal ones, are reported. Since the mechanisms of cereulide toxin uptake and translocation within the body as well as the mechanism of its toxic action are still unknown, we used a porcine model to investigate the uptake, routes of excretion and distribution of cereulide within the host. Pigs were orally challenged with cereulide using single doses of 10 to 150 µg cereulide kg-1 body weight to study acute effects or using daily doses of 10 µg cereulide kg-1 body weight administered for 7 days to investigate effects of longtime, chronic expose. Our study showed that part of cereulide ingested with food is rapidly excreted with feces while part of the cereulide toxin is absorbed, passes through membranes and is distributed within the body. Results from the chronic trial indicate bioaccumulation of cereulide in certain tissues and organs, such as kidney, liver, muscles and fat tissues. Beside its detection in various tissues and organs, our study also demonstrated that cereulide is able to cross the blood-brain-barrier, which may partially explain the cerebral effects reported from human intoxication cases. The neurobehavioral symptoms, such as seizures and lethargy, observed in our porcine model resemble those reported from human food borne intoxications. The rapid onset of these symptoms indicates direct effects of cereulide on the central nervous system (CNS), which warrant further research. The porcine model presented here might be useful to study the specific neurobiological effect in detail. Furthermore, our study revealed that typical diagnostic specimens used in human medicine, such as blood samples and urine, are not suitable for diagnostics of food borne cereulide intoxications. Instead, screening of fecal samples by SIDA-LC-MS may represent a simple and non-invasive method for detection of cereulide intoxications in clinical settings as well as in foodborne outbreak situations.